Clinicopathological Prognostic Factors and Chemotherapeutic Outcome for Two Histopathological Types of Ampulla of Vater Adenocarcinoma - Xia, Tao; Wu, Xiaosan; Mou, Yiping; Xu, Yunyun; Zhou, Yucheng; Lu, Chao; Zhu, Qicong; Jin, Weiwei; Chen, Yuan (Frontiers in Oncology, 2021)
Background: Adenocarcinoma of the ampulla of Vater (AAV) is standardly treated using a complex operation, a pancreatoduodenectomy (PD), to remove the tumor. However, discision-making in AAV clinical treatment remains difficult due to the broad range of AAV types, outcomes, and responses to special chemotherapeutics. Thus, this study aimed to explore clinicopathological prognostic factors associated with overall survival, as well as post-chemotherapeutic effects related to curative resection of AAV. Methods. We retrospectively reviewed data for clinicopathological outcome of 47 patients diagnosed with AAV that had underwent a PD. Overall survival probabilities were obtained using the Kaplan–Meier estimate method and a Cox proportional hazards model. Results. Forty-five patients underwent LPD (laparoscopic pancreatoduodenectomy) and two patients underwent PD. The patient group was composed of 31 males (66%) and 16 females (34%) with a mean age of 65（34-91）years. We selected 45 patients for long-term survival analysis. One- and three- year overall survival rates after resection were 97.6% and 58.9% respectively. The median survival was 37.7 months for the intestinal-type and 26.9 months in pancreatobiliary-type ampullary tumors. Serum carbohydrate antigen (CA) 19-9 greater than 37 U/ml (HR 0.140, P=0.007), perineural invasion (HR 0.141, P=0.003), and classification as pancreatobiliary-type (HR 6.633, P=0.006) were independently associated with poor survival. Serum carcinoembryonic antigen (CEA) greater than 5 ug/ml (P=0.031), serum CA 19-9 greater than 37 U/ml (P=0.002), tumor sizes greater than 2.5cm (P=0.002), and positive perineural invasion (P=0.003) were all associated with a poor prognosis in the histopathological subgroup. Serum CA 19-9 greater than 37 U/ml (P=0.002) and positive perineural invasion (P=0.001) were significantly associated with poor survival in of patients with intestinal-type ampullary tumors. Serum CEA greater than 5 ug/ml (P=0.013) and tumor sizes greater than 2.5cm (P=0.002) were significantly associated with poor survival in patients with pancreatobiliary-type ampullary tumors. Conclusions: Pancreatobiliary-type ampullary tumors were associated with poor survival. Serum CA 19-9 in the intestinal-type and CEA in the pancreatobiliary-type were significantly associated with poor survival. Ajuvant chemotherapy could not predict the survival of AAV patients.